EFEKTIVITAS RUMPUT BEBEK (Lemna minor) DALAM PENYISIHAN KADMIUM (Cd) DAN CHEMICAL OXYGEN DEMAND (COD) PADA LINDI TPA SAMPAH GAMPONG JAWA KOTA BANDA ACEH - Juliansyah Harahap; Irhamni; Nazri Adhlani; T. Muhammad Ashari (Program Studi Teknik Lingkungan Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh, 2022)
Lemna minor plant have the ability to reduce pollutant levels in Landfill leachate. The use of Lemna minor in leachate treatment was considered effective in degrading Cd and COD pollutants. The objective of this study was to determine the effectiveness and absorption rate of Lemna minor in degrading heavy metal Cd and reducing COD levels in Gampong Jawa Landfill leachate. This study used the phytoremediation method on a laboratory scale, and the leachate sampling method used the grab sampling technique. In testing both parameters, two types of test variations were carried out. First, in Reactor I, it was carried out without using an aerator, and in Reactor II, the test was carried out with the addition of an aerator. For duration, the variations of retention time were used are the third, sixth, ninth, and 12th days. The weight of the Lemna minor were used in each reactor was 35 grams for a leachate volume of 5 Liters. The results showed that Lemna minor was able to reduce pollutant levels in the Gampong Jawa Landfill leachate with the most optimal proportion of 15.92% for the heavy metal Cd, and 94.68% for the organic pollutant COD. Treatment on the 12th day for tests carried out in reactors that have an aeration system was the most effective variation in reducing the levels of Cd and COD parameters. Keywords : Lemna minor, Landfill Leachate, Phytoremediation